Tourists in Space A Practical Guide - Seedhouse, Erik.; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Praxis, 2008)
Recent surveys have provided new and updated information into public insights of the nascent space tourism industry. Erik Seedhouse uniquely explores in detail the cutting-edge technologies, spacecraft capabilities, launch vehicles and the training that will define this commercial enterprise and also provides a manual for future suborbital and orbital private space explorers. This overview of the space tourism market is based upon choices the spaceflight participant must make, such as choice of agency, mode and spaceport. A detailed explanation is given of the medical requirements for spaceflight participants, with special reference to potential waiver criteria. Over half of the book is a comprehensive astronaut training/instructional manual that addresses each of the 15 subjects required for suborbital and orbital flight.
Strapping rockets to dreams: The significance of SpaceShipOne -- Suborbital company profiles, technology drivers, and mission architecture -- Medical and training requirements for suborbital flight -- Orbital flight: The orbital experience, company profiles, mission architectures, and enabling technologies -- Medical certification: Spaceflight participant medical standards and certification -- Training for orbital flight -- Commercial applications of space tourism -- Advanced space tourism -- Epilogue.
Keywords: Aerospace engineering; Astronautics; Astronomy; Observations, Astronomical; Astronomy—Observations.; Medicine; Space sciences; Aerospace Technology and Astronautics; Popular Science in Astronomy; Astronomy, Observations and Techniques; Medicine/Public Health, general; Space Sciences (including Extraterrestrial Physics, Space Exploration and Astronautics).